Distance Learning For Music Practice In College: Benefits, Drawbacks, And Challenges - Setiarini, Agnes Tika (Universitas Negeri Medan, 2021)
The COVID-19 pandemic has impacted all sectors of human life globally, including the world of education. The world of education is forced to adapt by implementing a distance learning system to limit the mobility of educators and students. Program Studi D4 Penyajian Musik ISI Yogyakarta is one of the educational institutions that conduct distance learning. As a vocational education institution, ISI Yogyakarta helds many music practice courses to support its students' skills. This research aims to determine the benefits, drawbacks, and challenges of the distance learning system in music practice courses. This research is a qualitative study with 2 methods of data collection, namely in-depth interviews and questionnaires. Questionnaires were distributed to the respondents which are active students of the Prodi D4 Penyajian Musik, ISI Yogyakarta and will be confirmed by the results of in-depth interviews with the subject lecturers. The research results were formulated using the Miles & Huberman concept, namely: (1) data reduction; (2) data presentation; and (3) drawing conclusions (Miles & Huberman, 1984). The results of the study are concluding sentences about the benefits, drawbacks, and challenges of the distance learning method. These conclusions will be the basis for developing recommendations for the most effective distance learning process for the form of music practice lectures.